Urbanisation: A case study of overcrowding on Chinese flats dwellers - Anonymous, - (1982)
The aim of this academic exercise is to look into same of the socio-economic and psychological aspects of high-rise urban living and to discuss the effects of overcrowding if any on the Chinese residents. For this purpose, a total of 60 Chinese respondents are chosen as my sample with 30 from each block of the Shaw Read flats. As this will be an in depth study on the effects of overcrowding, I have employed an exploratory method to gain an insight on the life of the respondents and also to discover the effects if any on the life of these respondents that is in terms of health, family relations, kindship, child development and neighboring interactions. Later a comparison of the findings of this study with those other related studies carried out in Western countries will be presented. The first chapter will touch on the aspect of urbanization generally, the housing situation in Malaysia and Federal Territory, the objective and contributions of this study and lastly the review of literature. Chapter two concentrate wholly on the methodology employed with regard to the sample selection, the interview schedule, the interview and the problems encountered during the survey. The social economic conditions of flat dwellers as well as the physical structure of the building is presented in chapter three. A discussion in relation to the effects of overcrowding on several aspects of living will be touched on in chapter four whereas the conclusion is included in the fifth and final chapter.